a: \(P\left(x\right)+Q\left(x\right)=6x^4-11x^3+2x^2-\dfrac{1}{4}x-\dfrac{1}{4}\)
\(P\left(x\right)-Q\left(x\right)=4x^5-7x^3-6x^2-\dfrac{1}{4}x+\dfrac{1}{4}\)
b: \(P\left(0\right)=-2\cdot0^2+3\cdot0^4-9\cdot0^3-\dfrac{1}{4}\cdot0+2\cdot0^5=0\)
=>x=0 là nghiệm của P(x)
\(Q\left(0\right)=4\cdot0+3\cdot0-2\cdot0-2\cdot0-\dfrac{1}{4}=\dfrac{-1}{4}\)
=>x=0 không là nghiệm của Q(x)
c: \(Q\left(-1\right)=4\cdot1+3\cdot1-2\cdot\left(-1\right)-2\cdot\left(-1\right)-\dfrac{1}{4}\)
\(=7+2+2-\dfrac{1}{4}=11-\dfrac{1}{4}=\dfrac{43}{4}\)